2017
DOI: 10.1016/j.jaci.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 dysregulates regulatory T cells and impairs established immunologic tolerance in the lungs

Abstract: Background Airway exposure to environmental antigens generally leads to immunological tolerance. A fundamental question remains: why is airway tolerance compromised in patients with allergic airway diseases? Interleukin (IL)-33 promotes innate and adaptive type 2 immunity and may provide the answer to this question. Objective The goal of this study was to investigate the roles IL-33 plays in altering regulatory T (Treg) cells in the lungs and in affecting previously established airway immunological tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
93
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 65 publications
6
93
3
3
Order By: Relevance
“…Although IL‐33 is well recognized as a permissive influence in the development of autoimmune diseases involving the airways, the mechanisms by which it does this remain unclear. IL‐33 is able to promote the activity of immune cells while disabling regulatory T‐cells, activities that might sever immunological tolerance . IL‐33 is known to be produced principally by alveolar type II epithelial cells, and is rapidly released following activation or damage of the cells by viruses, allergens and other environmental insults impacting on the airways .…”
Section: Discussionmentioning
confidence: 99%
“…Although IL‐33 is well recognized as a permissive influence in the development of autoimmune diseases involving the airways, the mechanisms by which it does this remain unclear. IL‐33 is able to promote the activity of immune cells while disabling regulatory T‐cells, activities that might sever immunological tolerance . IL‐33 is known to be produced principally by alveolar type II epithelial cells, and is rapidly released following activation or damage of the cells by viruses, allergens and other environmental insults impacting on the airways .…”
Section: Discussionmentioning
confidence: 99%
“…When exposed to IL‐33, ST2 + Treg cells proliferated and upregulated GATA3 and ST2 expression . IL‐33‐stimulated GATA3 + Treg cells, but not GATA3 − Treg cells, expressed Il5 and Il13 mRNA, and were capable of producing IL‐5 and IL‐13 proteins . Furthermore, using an in vitro co‐culture assay, IL‐33 was shown to impair the ability of Foxp3 + Treg cells to suppress the proliferation of effector CD4 + T cells.…”
Section: Il‐33 In Adaptive Immunitymentioning
confidence: 98%
“…Treg cells are critically involved in immune homeostasis and tolerance to innocuous antigens . Under basal conditions, constitutive ST2 expression was observed in subsets of CD4 + Foxp3 + Treg cells in various tissues, including those in the lung and gastrointestinal tract . Interestingly, these ST2 + Treg cells also expressed the canonical Th2 transcription factor GATA3.…”
Section: Il‐33 In Adaptive Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…RSV infection impaired immune tolerance by inducing phenotypic changes in Foxp3 + Treg cells, including GATA-3 expression, Th2 cytokine production, and loss of suppressive functions, in an IL-4-dependent pathway [19]. The potential of IL-33 in overcoming acquired immune tolerance was confirmed recently [54]. It was revealed that Foxp3 + Treg cells express the IL-33 receptor ST2, the expression of which was enhanced by the ligand, that IL-33 evoked Th2-like properties in those cells by inducing GATA-3 expression and the synthesis of Th2 cytokines associated with the loss of suppressive function, and that intranasal IL-33 administration to tolerized mice (during or after sensitization) caused allergen-induced airway inflammation.…”
Section: Discussionmentioning
confidence: 99%